An orthorhombic polymorph of 2-(1,3-benzothiazol-2-yl)-6-ethoxyphenol - Kargar, Hadi (International Union of Crystallography, 2012)
In the title molecule, C(15)H(13)NO(2)S, an intramolecular O—H⋯N hydrogen bond forms an S(6) ring motif. The benzothiazole ring system and the benzene ring form a dihedral angle of 8.9 (3) Å. In the crystal, molecules are linked by weak C—H⋯O hydrogen bonds, forming chains along the b axis. In addition, π–π interactions [centroid–centroid distances = 3.772 (4) and 3.879 (4) Å] are observed.